PERENCANAAN TANGKI SEPTIK KOMUNAL DI DESA SUWARU, KECAMATAN PAGELARAN, KABUPATEN MALANG, JAWA TIMUR - Teguh Budiaji Setjo; Satyanto Krido Saptomo; Yanuar Chandra Wirasembada (Departemen Teknik Sipil dan Lingkungan, IPB University, 2016)
Environmental sanitation problems that occurred in Suwaru is septic tanks build too close to water sources such as wells and domestic waste disposal directly into the river. The purpose of this study is to determine the communal septic tank to achieve optimum and effective placement for the people in Suwaru, while also making the design communal septic tanks and leach fields communal septic tanks. The exact location of the study conducted in Suwaru, Pagelaran, Malang. The communal septic tank designed by four steps. These steps are estimating the population, calculating the dimensions of communal septic tanks, land mapping at the site plan and creating detailed engineering design (DED) of a communal septic tank. Septic tanks planned split into two service areas taking into account the difference in elevation of the service area. According to population projections, draining time (N) 5 years. Dimensions to accommodate the volume of waste that must be provided, with a height assumption of the septic tank is 4.5 m, obtained length is 10 m and width is 5 m to both septic tank.